REGISTRATION OF BUSINESS LICENSE BATAM FREE TRADE ZONE AUTHORITY CV. MITRA ANUGERAH SINERGI IN BP SYSTEM AND CEISA SYSTEM CUSTOMS - Titin Ervina; Yudi Kornelis (Universitas Internasional Batam, 2022)
Batam City is a KPPB or FTZ area which is determined in accordance with Government Regulation (PP) No. 44 of 2007 concerning Free Trade Areas and Free Ports. Batam City is special within the jurisdiction of the Unitary State of the Republic of Indonesia which is separated from other customs areas, because it gets exemption from import duties such as Value Added Tax (PPN), Personal Tax and Luxury Goods (PPnBM). The institution or agency that is appointed and established in the KPPB or FTZ area is the Concession Agency (BP), Batam City is called BP Batam. Entrepreneurs who carry out business activities in the KPPB or FTZ area are required to have a business permit for the concession area issued by the Batam City Concession Board. BP's regional business permit is a formal requirement for customs activities such as international, domestic, and regional KPPB or other FTZ imports at Customs. The executor in this PKM implementation activity explains information to partners about the importance of having a BP Batam area business permit as the identity of a business entity in carrying out customs activities and to obtain legal certainty as a business entity domiciled in Batam City. the main requirement in making a BP Batam area business permit. After all documents are complete, the next step is to submit an application through the Goods Entry Information System (SIKMB). In addition to requiring to have a BP Batam Area Business Permit registered by entrepreneurs who will make deliveries by water, sea, air through ports, airports and other official postal places, they must have a system issued by Customs and Excise with independent and correct registration, namely the User Portal. Services and Ceisa Online.Registration of the Service User Portal and Ceisa Online can be done at the entrepreneur's place, after registering and being registered as a user, you can carry out general activities such as issuing and importing goods from LDP, KB, TLDDP